CURA PERSONALIS SEBAGAI JALAN PENDIDIKAN TRANSFORMATIF: SEBUAH TINJAUAN LITERATUR SISTEMATIS DALAM VISI IGNASIAN - Astu, Tomas Becket Pramudita Praba (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
In education, especially secondary education, attention to the formation of students' personalities as whole human beings is crucial. Cura personalis, a distinctive principle in Ignatian education, provides a pedagogical approach that emphasizes personal and reflective accompaniment throughout the process of student growth and transformation. This study is a Systematic Literature Review of 13 selected scientific articles from Google Scholar during the period 2015–2025, using the PRISMA framework and Boolean techniques. The results of the study indicate that cura personalis plays a significant role in transformative education, encompassing spiritual, pedagogical, and social dimensions. In addition to being a relational approach, cura personalis has been proven to be operationalized in online learning, mentoring, discernment, and value-based leadership. This study also highlights the gap in empirical measurement and its application outside Jesuit institutions. This study aims to affirm the relevance and urgency of developing cura personalis as a path of education that liberates and humanizes students. This study also aims to provide a conceptual foundation for its broader application in the context of secondary education.